Peran Association Of South East Asian Nations (ASEAN) Dalam Menyelesaikan Sengketa Laut China Selatan - Sarah Nursyifa M Nusa; Irma Halima Hanafi; Popi Tuhulele (Faculty of Law Universitas Pattimura, 2023)
ASEAN as a regional organization whose members include most of the countries involved in this dispute, has an important role in trying to reduce tensions and maintain stability in the region. There are provisions in the 1982 Law of the Sea Convention regarding the reclamation of the PRC which has given rise to various interpretations. The court found that there was no historical evidence that China controlled and dominated natural resources alone in the South China Sea. It was also found that China has caused serious damage to the coral reef environment by building artificial islands. Although ASEAN is not a party directly involved in this dispute, the organization has an important role in helping manage the conflict and promoting norms of behavior that are binding on all parties involved. The research method used is normative juridical research. The problem approach method used is the Law approach, Concept approach and Case approach. The use of legal source materials consists of primary and secondary legal materials to discuss problem formulation. The research results show that: The mechanism for resolving disputes within the Association of South East Asian Nations (ASEAN) is carried out peacefully through dialogue, consultation and negotiation. Member countries involved in a dispute can resolve the dispute using good offices, conciliation or mediation mechanisms. Second, ASEAN's role in resolving South China Sea disputes involving third countries through the development of a Code of Ethics in the South China Sea (COC), which began with the signing of the Declaration on the Zone of Peace, Freedom and Neutrality (ZOPFAN) for recognition and respect as a zone. peace, freedom and neutrality by external powers while expanding cooperation. So it is hoped that ASEAN can make further efforts specifically so that this issue can have a binding agreement between all countries concerned in these regions.